2023
DOI: 10.3892/ol.2023.13761
|View full text |Cite
|
Sign up to set email alerts
|

Application of robotic surgery and traditional laparoscopic surgery in lymph node dissection for gynecological cancer: A meta‑analysis

Abstract: Since the advantages of robotic surgery and laparoscopic surgery in the number of lymph node resections are not well understood, this meta-analysis used evidence-based medicine to assess the difference in the number of lymph nodes retrieved in gynecological cancer between the two surgical methods to guide clinical treatment. In the present meta-analysis, the Pubmed, Embase, Cochrane, China National Knowledge Infrastructure and Wanfang libraries were searched for articles that were published from the time of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Our findings suggest that RRH is superior than LRH in terms of the number of pelvic lymph nodes dissected. Prior research has also indicated that robotic surgery yields superior results in lymph node dissection for gynecological cancer compared to traditional laparoscopic surgery ( 25 , 26 ). This is due to the improved clarity and balance of RRH, as well as the capability of its endoscopic operating device to replicate the movement of the human wrist.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that RRH is superior than LRH in terms of the number of pelvic lymph nodes dissected. Prior research has also indicated that robotic surgery yields superior results in lymph node dissection for gynecological cancer compared to traditional laparoscopic surgery ( 25 , 26 ). This is due to the improved clarity and balance of RRH, as well as the capability of its endoscopic operating device to replicate the movement of the human wrist.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the size and metastasis of GCs, imaging modalities such as ultrasound, computed tomography (CT), magnetic resonance imaging (MRI), and positron emission tomography (PET) scans are routinely employed [ 11 ]. Also, various biopsy techniques, including colposcopy [ 12 ], endometrial biopsy [ 13 ], hysteroscopy [ 14 ], and laparoscopy [ 15 ], are utilized to procure tissue samples from suspected tumors or abnormal regions for further analysis and confirmation. Molecular tests can identify specific biomarkers associated with GCs, such as human papillomavirus (HPV) testing for cervical cancer or genetic testing for ovarian cancer [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%